Kondisi Lingkungan Perairan Budi Daya Rumput Laut di Desa Arakan, Kabupaten Minahasa Selatan - Burdames, Yanis; Ngangi, Edwin L.A. Ngangi2 L.A (Universitas Sam Ratulangi, 2014)
The purpose of the study was to evaluate the present feasibility of seaweed cultivation area at the waters of Arakan village. Research method used was observation. Observation station consisted of 1) near residential area, 2) at seaweed culture area, 3) around mangrove ecosystem. Data collected included area sheltering, bottom substrate, pH, salinity, flow rate, water depth. Measurement of water quality was conducted in the morning and afternoon. Data was analyzed descriptively and then compared with the water quality tables eligibility for seaweed cultivation by Bakosurtanal 1996. Research results illustrated that cultivation areas at all station were feasible, water quality at station 1 was very feasible and station 3 was less feasible. pH and salinity at all station were very feasible, flow rates at station 1 and 3 were less feasible while at station 2 was very feasible, water depth was very feasible, and water temperature was categorized as feasible to very feasible. It was concluded that the present condition of the waters at Arakan Village is still suitable for seaweed aquaculture. Keywords: Desa Arakan, seaweeds, water quality, area feasibility